Den Nächsten kennen wie sich selbst. Konfessionskundliche Einblicke und ökumenische Ausblicke

Wittgenstein, Ludwig, Wiener Ausgabe, Bd. 10,3: Zettelsammlung aus den Synopsen der Manuskriptbände I bis X, hg. v. Michael Nedo, Vittorio Klostermann: Frankfurt a.M. 2024, xv, 479–726 S. - Peckhaus, Volker (zbMATH Open, Zbl. 079505172)

2024 Global Tax Complexity Survey - Gerdes, Kristin; Harst, Simon; Schanz, Deborah; Sureth-Sloane, Caren

Das Profilstudium Gute gesunde Schule unter dem Blickwinkel der beruflichen Praxis - Decker, Claudia; Waltert, Carolin; Kehne, Miriam; Satzinger, Nicole; Strotmeyer, Anne; Tarampouskas, Antje; Vlachos, Maximilian; Wobbe, Lena (Gesundheitskompetenzen in Hochschulen entwickeln - Studierende für ihre berufliche Zukunft stärken,)

"Ich glaub, ich hab's verstanden." - Verstehensillusion bei Erklärvideos - Hörnlein, Madeleine; Riese, Josef; Kulgemeyer, Christoph (Lernen, Lehren und Forschen im Schülerlabor. Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik 2024)

Life cycle engineering of lightweight structures in vehicles for on-demand mobility services - Ostermann, Moritz; Dierkes, Eric; Marten, Thorsten; Tröster, Thomas (Cleaner Engineering and Technology)
To reduce transport-related environmental impacts, innovative mobility system approaches such as on-demand services are being developed. These can include operating vehicles that differ regarding their characteristics and application profile from privately owned cars in motorized individual transport. Studies on life cycle assessment and life cycle engineering of vehicle lightweight structures are mainly limited to these privately owned cars and the impact category of climate change. In this paper, a method for life cycle assessment-based engineering of lightweight structures in vehicles for various mobility system applications, including on-demand mobility services, is developed. The method enables the holistic life cycle assessment of lightweight structures in different mobility system applications considering parameter changes at the upstream products, component, subsystem, vehicle and mobility system levels, as well as the integration of results into engineering activities. A case study is used to show that the vehicle and mobility system application of lightweight structures can significantly influence their environmental impacts and the selection of ecologically preferable product designs. The application in vehicles for on-demand mobility services can lead to an increase in absolute use stage energy demand and environmental impacts compared to applications in privately owned vehicles for motorized individual transport. However, normalized to the transport performance provided, the lifecycle environmental impacts of structural components in vehicles for on-demand mobility services can be lower than in vehicles for motorized individual transport. The paper contributes methodically and with quantitative results to improved decision making in life cycle engineering activities for lightweight structures in mobility system applications.
Keywords: Life cycle assessment; Life cycle engineering; Lightweight design; On-demand mobility; Shared mobility; Mobility services

[Rezension zu:] Clara Fischer, Experimentierfeld Versepos (1918‒1933). Mit Studien zu Thomas Mann und Alfred Döblin. Wallstein, Göttingen 2024 - Elit, Stefan (Arbitrium)

ABIS 2025 – 29th International Workshop on Personalization and Recommendation - Neumayr, Thomas; Yigitbas, Enes; Augstein, Mirjam; Herder, Eelco; Stojko, Laura; Strecker, Jannis; Seitz, Julia (Proceedings of the Mensch & Computer (2025))

Perspectives on Contexts and Adaptations for Cross-Reality - Krings, Sarah Claudia; Yigitbas, Enes; Sauer, Stefan (Proceedings of the 29th International Workshop on Personalization and Recommendation)

Workarounds as a Cause of Mismatches in Business Processes—Insights from a Multiple Case Study - Bartelheimer, Christian; Löhr, Bernd; Reineke, Malte Fabian; Aßbrock, Agnes; Beverungen, Daniel (Business & Information Systems Engineering)
Process mining has been established as a data-driven approach to analyze and improve business processes based on event data documented in event logs. A core assumption for meaningful analyses is that event data accurately represent the real-world execution of business processes in an organization. However, anecdotal evidence and recent case studies show that these aspects do not always align, and the business process management community is only beginning to investigate the mechanisms generating mismatches between process execution and event data. This study aims to identify the role of workarounds goal-directed deviations from standard processes performed by process participants to overcome obstacles– in this context. Through an inductive multiple case study of 13 workarounds in four organizations, three mismatch categories between event logs and real-world process execution related to workarounds are identified and explored. This study contributes to the literature by describing how workarounds can act as mechanisms that cause mismatches between process execution and event data, adding to the discussion on process drift and workaround mining. Furthermore, exploring the mismatch categories offers insights for practitioners and researchers on how to handle and interpret data quality issues in event data.

Nontoxic and Rapid Chemical Bath Deposition for SnO2 Electron Transporting Layers in Perovskite Solar Cells - Grotevent, Matthias J.; Kothe, Linda; Lu, Yongli; Krajewska, Chantalle J.; Shih, Meng-Chen; Tan, Shaun; Tiemann, Michael; Bawendi, Moungi G. (Chemistry of Materials)

Tax Disputes - The Role of Technology and Controversy Expertise - Dyck, Daniel; Lorenz, Johannes; Sureth-Sloane, Caren

Tax Compliance Management Systems in German Tax Audits - An Analysis of Practical Experiences - Schulz, Kim Alina; Sureth-Sloane, Caren
Recent regulatory changes and the adoption of the ‘DAC 7’ EU Directive have significantly increased the importance of Tax compliance management systems (Tax CMS) in German tax audits. Our interview-based study, which draws on the insights of experts from various sectors, including industry and commerce on the one hand side and tax advisors on the other hand side, reveals nuanced perspectives on the impact of Tax CMS on tax audits. Our results reveal that the number of Tax CMS in German firms has increased in recent years and that, in particular, the majority of large firms have implemented these control systems. From a firm’s perspective, there has been no discernible impact on the duration, scope, or focus of tax audits, nor the frequency of tax disputes or the number and size of tax refunds. However, tax practitioners in advisory firms report a slight positive change in the audit environment, with fewer tax disputes, and a more efficiency-driven approach to audit procedures, with an increase in process-oriented audits. These findings represent preliminary observations on the use and effectiveness of Tax CMS in tax audits. They provide early insights into the advantages and disadvantages of these systems. These findings are particularly relevant given the expected increasing role of Tax CMS in German tax audits, driven by ongoing regulatory developments.

Auferstehung. Zum 150. Geburtstag von Walter Courvoisier (1875-1931) - Schroeter-Wittke, Harald (Praktische Theologie)

Tanken. Zum 100. Todestag von Hjalmar Borgström (1864-1925) - Schroeter-Wittke, Harald (Praktische Theologie)

Chromophore Induced Effects in Iron(III) Complexes - Schmitz, Lennart; Argüello Cordero, Miguel A.; Al-Marri, Mohammed J.; Schoch, Roland; Egold, Hans; Neuba, Adam; Steube, Jakob; Bracht, Bastian Johannes; Bokareva, Olga S.; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
In the search for noble metal free photocatalytic systems, iron is the dream candidate. To increase excited state lifetimes of iron complexes, the multichromophoric approach is promising, combining organic chromophores with photoactive iron complexes, potentially enabling a reservoir effect. We present a series of chromophore-functionalized complexes based on the parental FeIII complex [Fe(ImP)2][PF6] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)). The four organic chromophores benzene, naphthalene, anthracene, and pyrene are attached to the ImP-ligand in para-position to the coordination site to systematically investigate the influence of the steric demand and electronic properties of the chromophore on charge transfer lifetimes as well as photodynamics. A thorough ground state characterization was conducted in addition to investigations of the excited state dynamics by transient absorption spectroscopy and streak camera emission measurements. The conclusions drawn are supported by extensive DFT calculations. The emission coefficients could be significantly improved by the addition of chromophores. After excitation of the complexes with larger chromophores, coplanarization of the backbone and complex motif occurs to stabilize the formal charge. This results in population of a superligand state that exhibits a much faster radiationless relaxation to the ground state compared to the parent complex, hindering a reservoir effect.
Keywords: Photo

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.
Keywords: Photo

Contrastive Verbal Guidance: A Beneficial Context for Attention To Events and Their Memory? - Singh, Amit; Rohlfing, Katharina J. (Cognitive Science)
Research suggests that presenting an action via multimodal stimulation (verbal and visual) enhances its perception. To highlight this, in most studies, assertive instructions are generally presented before the occurrence of the visual subevent(s). However, verbal instructions need not always be assertive; they can also include negation to contrast the present event with a prior one, thereby facilitating processing—a phenomenon known as contextual facilitation. In our study, we investigated whether using negation to guide an action sequence facilitates action perception, particularly when two consecutive subactions contrast with each other. Stimuli from previous studies on action demonstration were used to create (non)contrastive actions, that is, a ball following noncontrastive and identical (Over–Over or Under–Under) versus contrastive and opposite paths (Over–Under or Under–Over) before terminating at a goal location. In Experiment 1, either an assertive or a negative instruction was provided as verbal guidance before onset of each path. Analyzing data from 35 participants, we found that, whereas assertive instructions facilitate overall action recall, negating the later path for contrastive actions is equally facilitative. Given that action goal is the most salient aspect in event memory due to goal-path bias in attention, a second experiment was conducted to test the effect of multimodal synchrony on goal attention and action memory. Experiment 2 revealed that when instructions overlap with actions, they become more tailored—assertive instructions effectively guide noncontrastive actions, while assertive–negative instruction particularly guides contrastive actions. Both studies suggest that increased attention to the goal leads to coarser perception of midevents, with action-instruction synchrony modulating goal bias in real-time event apprehension to serve distinct purposes for action conceptualization. Whereas presenting instructions before subactions attenuates goal attention, overlapping instructions increase goal attention and reveal the selective roles of assertive and negative instructions in guiding contrastive and noncontrastive actions.

The Intrapreneur Identity Illusion: Unraveling the Identity Work of Intrapreneurs in Internal Corporate Venturing - Starmann, Frederic-Alexander; Tomin, Slawa; Hubner-Benz, Sylvia; Kabst, Rüdiger (Journal of Product Innovation Management)
ABSTRACT Intrapreneurs—employees participating in internal corporate venturing (ICV) programs—are vital in nurturing entrepreneurship within organizations. While existing literature has extensively studied ICV at the organizational level, research on individual‐level processes remains limited, particularly regarding intrapreneurs' identity‐related conflicts over time. However, to design programs and interventions that unlock employees' creative potential and promote innovation, it is crucial to understand these individual dynamics. We conducted an 18‐month longitudinal study of 21 intrapreneurs within an ICV program, developing a process model and theory of intrapreneurs' identity work. We find that aspiring intrapreneurs construct an “idealized entrepreneur identity” that fundamentally conflicts with their employee identity. To maintain a coherent sense of self, they either safeguard their emerging entrepreneur identity by denying corporate dependence and eventually opposing the organization or they realign with their employee role, forsaking their intrapreneurial aspirations. These findings challenge the implicit assumption of a distinct intrapreneur identity, demonstrating how and why intrapreneurs struggle to construct a coherent and positively valued identity as intrapreneurs. We term this phenomenon the intrapreneur identity illusion and highlight its detrimental effects for both individuals and organizations. Our research contributes to understanding the individual‐level foundations of corporate entrepreneurship and offers broader implications for innovation management.

Unveiling the Impact of Cultural Value Orientations on Ideation Outcomes: Evidence From the International #EUvsVirus Hackathon - Krebs, Benjamin P.; Funck, Marieke; Tomin, Slawa; Wach, Bernhard; Kabst, Rüdiger (R&D Management)
ABSTRACT This study addresses the role of national culture in shaping hackathon teams' ideation outcomes. Drawing on the innovation and creativity literature and Schwartz’ theory of cultural value orientations, we propose that hierarchical values decrease the quality of ideas that teams develop over the course of a hackathon and that intellectual autonomy and mastery improve it. Using archival data, including pitch presentations from an international hackathon and data on cultural value orientations, we compiled a sample of 308 teams to investigate the influence of cultural value orientations and employed linear mixed‐effects regression analysis to test our hypotheses. We found that hierarchical cultural values are negatively associated with the quality of ideas, which suggests that hackathon teams that operate in such cultures suffer from a “liability of hierarchy.” We also found that teams from societies that emphasize mastery of the natural and social environment are more likely than other teams are to develop high‐quality ideas to tackle the (grand) challenges that hackathons address. We found no relationship between intellectual autonomy and idea quality. The study findings support the notion that culture manifests in hackathon teams' behavior and so shapes the quality of ideas they develop, thus laying the foundation for success or failure.